Self-assembling nanoarchitectonics of low dimensional semiconductors for circularly polarized luminescence - Xiongbin Wang; Xuanyu Zhang; Huan Liu; Zikang Tang; Rui Chen (Journal of Materiomics, 2023)
Recently, the development of materials with circularly polarized luminescence (CPL) has attracted numerous attentions owing to their potential applications in various fields. Among diverse mechanisms for the origin of chiroptical properties in low dimensional semiconductors (LDS), the self-assembly approach provides a powerful technique for acquisition of strong chiroptical activity. Benefiting from this approach, LDS could be endowed with CPL in which the dissymmetry factor, a vital parameter for evaluating the performance of CPL, could be greatly improved. In this review, state-of-the-art of self-assembled LDS will be summarized. The current challenges and perspectives in this emerging field are also presented. This review could not only provide insights of the fundamentals of self-assembled chirality, but also shine light for designing CPL-active functional nanomaterials toward their applications based on novel optoelectronic devices.